Starting antidepressant use: a qualitative synthesis of UK and Australian data. Issue 12 (30th December 2015) - Anderson, Claire; Kirkpatrick, Susan; Ridge, Damien; Kokanovic, Renata; Tanner, Claire
Abstract : Objective: To explore people's experiences of starting antidepressant treatment. Design: Qualitative interpretive approach combining thematic analysis with constant comparison. Relevant coding reports from the original studies (generated using NVivo) relating to initial experiences of antidepressants were explored in further detail, focusing on the ways in which participants discussed their experiences of taking or being prescribed an antidepressant for the first time. Participants: 108 men and women aged 22–84 who had taken antidepressants for depression. Setting: Respondents recruited throughout the UK during 2003–2004 and 2008 and 2012–2013 and in Australia during 2010–2011. Results: People expressed a wide range of feelings about initiating antidepressant use. People's attitudes towards starting antidepressant use were shaped by stereotypes and stigmas related to perceived drug dependency and potentially extreme side effects. Anxieties were expressed about starting use, and about how long the antidepressant might begin to take effect, how much it might help or hinder them, and about what to expect in the initial weeks. People worried about the possibility of experiencing adverse effects and implications for their senses of self. Where people felt they had not been given sufficient time during their consultation information or support to take the medicines, the uncertainty could be particularly unsettling and impact on their ongoing views on and use of antidepressants as a viable treatment option. Conclusions: Our paper is the first to explore in-depth patient existential concerns about start of antidepressant use using multicountry data. People need additional support when they make decisions about starting antidepressants. Health professionals can use our findings to better understand and explore with patients' their concerns before their patients start antidepressants. These insights are key to supporting patients, many of whom feel intimidated by the prospect of taking antidepressants, especially during the uncertain first few weeks of treatment.